GITA ARDAYA - Agoeng Prasetyo (SURYA SENI, 2009)
A creation of art is inﬂ uenced by the artist life experiences. The more experience he has the more skillful he is. A composer is also inﬂ uenced by his/her background and the way he or she interprets phenomena around him/her. The idea can be form his or her imaginative experience, observation, exploration ofsocial life, religious matter, culture, tradition and nature. The composition of Gita Ardaya  is a music composition containing basic values based on sense of honesty to life that brings them to prosperity.This composition consists of ﬁveparts namely: (1) Byar, means morning; (2) Pamitan,meansask for leaving, farewell; (3) Taberi, means diligent or work hard; (4)Titiyoni,means midnight; (5) Loka, means the universe. The process of making this music involves a lot of instruments both westernand eastern musical instruments. The composition does not state a tone or note, and the core sound of the music is arranged and creates new image.Keywords: meaning, expression, honesty, and sounds.